PERANAN MIKROBA ENDOFIT UNTUK PENGEMBANGAN OBAT ANTI KANKER - Siti Rofida (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2011)
Natural product that has developed as anticancer drugs are consists from secondary metabolites that has isolated from plant, ocean plant and microorganisms. To maintain its productivity, must be concerned to the cultivation of the medicinal plants. Medicinal plants need time to grow and producing secondary metabolites that would be isolated, so that the production of secondary metabolites compound from plant is very limited. The plants that infected by endophytic fungi be able to grow faster than the normal plants. Endophytic fungi also have ability producing secondary metabolites compound that produced by the host plant. Taxol, podophyllotoxin and camptothecin are compounds that proved has anticancer activity. Endophytic fungi have also proved increasing the production of the compound.